KAJIAN PEMBANGUNAN SISTEM DRAINASE BERWAWASAN LINGKUNGAN DI KAWASAN PERUMAHAN - Nurhapni, Nurhapni; Burhanudin, Hani (Jurnal Perencanaan Wilayah dan Kota, 2011)
Development will basically change the natural conditions, the establishment of residential land will make a watertight result in disruption of the hydrological balance. Increased run off due to the closing of the land by residential buildings should be designed so that the flow will not quickly disappear but could still be converted into ground water reserves. Filosopfi Green Building build inpirasi how housing can be designed environmentally friendly. Channeling rain water (drainage) environmentally sound residential area enabled it pursued a number of run-off water (run off) the dialirkannya. Pavement drains, yard, road construction and water seeped infiltration wells with RTH is a reliable means to realize an environmentally friendly housing. Hydrologic analysis is required as a basis for converting rainwater that falls in a residential area into a run-off discharge is generated. By obtaining subsequent runoff discharge channel hydraulic analysis was performed to evaluate the use of construction of water channels that qualify are eligible to do. Hydrologic analysis is also needed to calculate the number of facilities required infiltration wells. Meanwhile, to calculate RTH needs and building water passes used standards that can be applied to the residential areas. Keywords: systems, drainage, environment, housing